Analysis of hepatitis B virus integration identifies KMT2B as a novel cancer‐related gene in pancreatic cancer - Mengge Li; Huimin Li; Dejun Liu; Shunan Liu; Hui Yuan; Yan Wu; Min Du; Yuan Fang; Jin Li; Hui Cong; Dan Zhao; Chunsun Fan; et al. (Clinical and Translational Medicine)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive malignancy with few well‐established risk factors. Emerging epidemiological evidence suggests a link between hepatitis B virus (HBV) infection and PDAC. However, the underlying mechanisms remain unclear. Methods High‐throughput sequencing‐based approach was employed to identify HBV integrations in tumour and para‐tumour tissues of PDAC. The biological functions of KMT2B were evaluated in PDAC cell lines as well as in subcutaneous and orthotopic mouse models of PDAC. Chromatin immunoprecipitation sequencing and RNA sequencing were used to identify the pathway involved in PDAC development. Results HBV integration was detected in approximately one‐third of HBV DNA‐positive PDAC and adjacent para‐tumour tissues. A total of 425 viral‒host junctions were identified, with the majority located in intergenic regions (51.29%), followed by introns (43.29%) and exons (2.35%) of the human genome. Lysine methyltransferase 2B (KMT2B, also known as MLL4), a gene frequently targeted by HBV integration in hepatocellular carcinoma, was also found to be interrupted by HBV in PDAC. KMT2B was significantly upregulated in PDAC and promoted malignant behaviours both in vitro and in vivo. Mechanistically, KMT2B exerts its oncogenic effects by regulating the downstream target gene FYN through histone H3K4 trimethylation, leading to the activation of the PI3K/Akt signalling pathway. Conclusion HBV integration is a common event in HBV‐related PDAC and KMT2B has been identified as a novel PDAC‐related gene. Key points Hepatitis B virus (HBV) integrates in both tumour and adjacent para‐tumour tissues of pancreatic ductal adenocarcinoma (PDAC). KMT2B, a target gene of HBV integration, promotes PDAC proliferation and metastasis in vivo and in vitro experiments. KMT2B exerts its oncogenic effects by regulating the downstream target gene FYN via histone H3K4 trimethylation, activating the PI3K/Akt signalling pathway.